Recent Trends in Security and Privacy of Sensitive Data in Cloud Computing - P, Dayaker; Reddy T, Chandrasekhara; Diana P, Honey; Mallikarjun Reddy, A. (International Journal of Engineering and Technology, 2018)
Cloud Computing (CC) is reforming many biological communities by furnishing associations with registering assets including simple organization, network, design, Romanization, and adaptability. This change in perspective raises an expansive scope of security and protection issues that must be thought about. Multi-tenure, loss of control, and trust are entering challenges in cloud processing conditions. This paper surveys the current advancements and a wide show of both earlier and frontier extends on cloud security and protection. We classify the current look into as per the cloud reference engineering coordination, asset control, physical asset, and cloud benefit administration layers, in spite of inspecting the current improvements in security safeguarding touchy information approaches in CC, such as, security risk demonstrating and protection upgrading conventions and arrangements.Â